2001
DOI: 10.1164/ajrccm.163.5.2003162
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Chlamydia pneumoniae Antibodies in Patients with Asthma

Abstract: The worldwide increase in asthma incidences and the impact of the disease on public health care have led to new investigations of the cause of the disease. Besides well-defined environmental causes, accumulating evidence suggests that respiratory tract infections play an important role in the pathogenesis of asthma. Among these microorganisms Chlamydia pneumoniae is an intracellular pathogen causing persistent infection. Chlamydia pneumoniae infection has been discussed as possibly inducing the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…One of the most important is the low rate of false-positive results in the control group. The rate of 3% compares favourably to serological studies of Chlaymdia pneumoniae in COPD and asthma [15,16].…”
Section: S Ewigmentioning
confidence: 72%
“…One of the most important is the low rate of false-positive results in the control group. The rate of 3% compares favourably to serological studies of Chlaymdia pneumoniae in COPD and asthma [15,16].…”
Section: S Ewigmentioning
confidence: 72%
“…It is possible that the study design employing spouse pairs, among who close proximity might favour higher rates of transmission, may have actually underestimated the degree of increased frequency of detection in asthmatic subjects. Several studies have shown a higher prevalence of antibodies to C. pneumoniae in asthmatic compared to normal control subjects [11,[25][26][27], and one study has shown a relationship to disease severity [12]. These studies have not been able to differentiate acute from chronic infection, although several have hypothesised the presence of chronic C. pneumoniae infection.…”
Section: Discussionmentioning
confidence: 99%
“…In another study 11 % asthmatic and 5 % control children found to have positive cultures for C. pneumoniae 3 . Although some results were controversial, several studies confirmed these findings 4,5,6 . Our study aimed to investigate the current situation in the seroprevalence of C. pneumoniae infection in Olomouc district in a group of atopic children with chronic cough and asthma compared with a control group of non-atopic children with non-specific symptoms, i.e., temperature above normal, abdominal pain, arthralgia, fatigue.…”
Section: Introductionmentioning
confidence: 93%